On endings American postmodern fiction and the Cold War - Grausam, Daniel, 1975- (University of Virginia Press, 2011)
What does narrative look like when the possibility of an expansive future has been called into question? This query is the driving force behind Daniel Grausam's On Endings, which seeks to show how the core texts of American postmodernism are a response to the geopolitical dynamics of the Cold War and especially to the new potential for total nuclear conflict. Postwar American fiction needs to be rethought, he argues, by highlighting postmodern experimentation as a mode of profound historical consciousness. On Endings significantly extends the project of historicizing postmodernism while returning the nuclear to a central place in the study of the Cold War.